Omegaverse or the forging of a fanfiction universe - Delgado Díaz, Luz Marina (2022)
This article explores the Omegaverse, a fictional universe created and developed by fans and amateur writers. Despite being born far from business logic, it has drawn the interest of the editorial industry, which now profits from its popularity. The analysis pays special attention to the Omegaverse’s formal features, for which it reconstructs its evolution from its beginnings in 2009 until 2021, both online and in print. The results confirm that its development has resulted in the birth of a narrative matrix of its own, inscribed the fantasy genre, which facilitates its dissemination and serves as a guide to create and promote its followers’ expectations. Fanfictions have in the Omegaverse a robust example of how their stories can be as captivating as those produced by the industry.